"If We Don't Define Our Roles, Someone Else Will": Professional Advocacy in School Counseling. (January 2019) - Havlik, Stacey; Ciarletta, Marie; Crawford, Emily
Professional advocacy in the field of school counseling is critical to promote the profession and ensure that school counselors are engaged in appropriate roles that are aligned with the American School Counselor Association (ASCA). To better understand how they are engaging in this important work, we interviewed and surveyed school counselors about their experiences with professional advocacy. Findings suggest that school counselors possess strengths and face challenges when advocating for their roles.